99 things you wish you knew before-- choosing adoption : your easy-to-read guide to adoption - Kasky, Robert A. (99 Series, 2012)
"If you have ever been interested in adoption--as a prospective adoptive family, a birth parent, or even as an adoption practitioner--this book is for you! It addresses the mysteries and myths that surround and permeate the adoption process, simplifying them for the non-lawyer and keeping the reader entertained all the while. Fear not the adoption process! The Kaskys, with their 60+ years of combined experience, efficiently answer all of your questions in a straightforward no-nonsense manner"--P. [4] of cover.